Karamat as Religious Legitimation: Ulama Authority in the Manuscript Sejarah Syekh Abdurrauf and Syekh Burhanuddin - Amrullah; Mamlahatun Buduroh; Hafiz Maruf Akbar (Center for Research and Development of Religious Literature and Heritage, 2026)
This study examines the manuscript Sejarah Syekh Abdurrauf and Syekh Burhanuddin, Dua Orang Pembangun Islam di Aceh dan Minangkabau, focusing onkaramatas a mechanism for constructing ulama authority. It employs a qualitative descriptive method integrating philological and critical hagiographical approaches, supported by the theoretical frameworks of charismatic authority and symbolic capital. The findings reveal three interrelated dimensions of authority construction: intellectual and legal authority, built through sanad, fatwa, riḥlah, and the Haramain–Aceh–Minangkabau scholarly network; spiritual and charismatic authority, constructed through kashf, adab, khidmah, the teacher's mandate, and extraordinary events; and social and institutional authority, represented through royal acknowledgment in Aceh and acceptance by customary elites within the Minangkabau nagari system. The analytical contribution of the manuscript lies in its representation of the transmission of authority from Sheikh Abdurrauf to Sheikh Burhanuddin across two distinct political and cultural settings, integrating these three dimensions within a single textual structure.karamatthus functions not merely as a collection of miraculous narratives, but as a textual mechanism that connects transregional scholarship, Sufi discipline, and institutional recognition within a specific Aceh–Minangkabau model of ulama authority.